Research methods in accounting - Smith, Malcolm (Los Angeles, California : Sage Publications, Incorporation, 2017)
Designed specifically for accounting students and researchers, Research Methods in Accounting is a unique text used by over 10,000 students that provides a thorough understanding of the research process. Using practical and real life examples from industry, it outlines the relevant methods that can be applied and offers a dedicated chapter on publishing your research. Suitable for students at advanced undergraduate and postgraduate levels, as well as accounting research practitioners.
Keywords: ACCOUNTING -- RESEARCH -- METHODOLOGY